Description, diagnosis, prescription: a critique of the application of co- evolutionary models to natural resource management. - Jeffrey, Paul; McIntosh, Brian S. (Cambridge University Press, 2006)
To support moves towards more sustainable modes of natural resource management, the research community has been engaged in an evaluation of paradigms, theories and methods which might provide useful and usable insights into such a complex problem set. A particularly influential family of theoretical models concerned with the processes and dynamics of species evolution has been adopted from the fields of biology and ecology. This paper scrutinizes the relevance of biological evolutionary theory to sustainable natural resource management beyond identification of the core analogy, namely that both natural resource management and ecological systems are characterized by multiple interacting elements requiring systemic interpretation. A review of the workings of co-evolutionary theory within its intellectual homeland of biology and ecology leads to a critical evaluation of its use as a descriptive model outside of these domains. Findings from this assessment identify a number of fractures in meaning as the co-evolutionary model is transferred between disciplinary fields, suggesting that the transposition has been conducted without sufficient rigour or consistency. A measured reinterpretation of the applicability of the co- evolutionary model to natural resources management is thereby undertaken. Using water management as a context, the paper posits a series of phenomena which might provide a focus for the application of the co-evolutionary model outside of biology and ecology. In conclusion, the paper argues that the research community needs to move beyond a consideration of the complex implications of co-evolutionary processes to the establishment of a firm, process-based definition of co-evolution as a type of change.
Keywords: co-evolution; natural resource management; socio-natural science; sustainability; water management